2002
DOI: 10.1002/ace.54
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative inquiry for adult learning

Abstract: Collaborative inquiry (CI) provides a systematic structure for learning from experience. Participants organize themselves in small groups to address a compelling question that brings the group together. In order to construct new meaning related to their question, collaborative inquirers engage in cycles of reflection and action, evoke multiple ways of knowing, and practice validity procedures. Typically, they balance exploration of inner experience with action in the world. CI is especially appropriate for pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 3 publications
0
46
0
Order By: Relevance
“…We thus follow a constructivist approach to education where learning takes place by students creating artefacts rather than assuming the passive role of a listener or reader. Our approach is based on a wide range of studies that have shown that with the right scaffolding competent learners benefit greatly from constructivist or learning-by-doing approaches [17][18][19]. The experiment-driven approach of FORGE contributes to fostering constructivist learning by turning learners into active scientific investigators, equipped with world-class experiment facilities.…”
Section: Building Interactive Learning Resourcesmentioning
confidence: 99%
“…We thus follow a constructivist approach to education where learning takes place by students creating artefacts rather than assuming the passive role of a listener or reader. Our approach is based on a wide range of studies that have shown that with the right scaffolding competent learners benefit greatly from constructivist or learning-by-doing approaches [17][18][19]. The experiment-driven approach of FORGE contributes to fostering constructivist learning by turning learners into active scientific investigators, equipped with world-class experiment facilities.…”
Section: Building Interactive Learning Resourcesmentioning
confidence: 99%
“…We thus follow a constructivist approach to education where learning takes place by students creating artefacts rather than assuming the passive role of a listener or reader. Our approach is based on a wide range of studies that have shown that with the right scaffolding competent learners benefit greatly from constructivist or learning-by-doing approaches [2][3][4]. The experiment-driven approach of FORGE contributes to fostering constructivist learning by turning learners into active scientific investigators, equipped with world-class experiment facilities.…”
Section: Building Interactive Learning Resourcesmentioning
confidence: 99%
“…The consensus within education is that after the Internet-induced revolutions in communication, business, entertainment, media, amongst others, it is now the turn of universities. Exactly where this revolution will lead is not yet known but some radical predictions have been made including the end of the need for university campuses 4 , while milder future outlooks are discussing 'blended learning' (combination of traditional lectures with new digital interactive activities). The consensus is however that the way higher education students learn is about to change radically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaborative inquiry has been used within the context of adult education 12,13 , teacher development 14 , and engineering education 15 to help individuals "systematically examine [their] own practice with a view to purposefully [advance] our understanding...based on evidence and concrete experience" 15 (p.6). This type of inquiry is typically comprised of cycles of reflection and action, whose form and timing are dependent on the purpose of the inquiry and the constraints of the group 11,12 .…”
Section: A Collaborative Inquiry Approachmentioning
confidence: 99%